An investigation on corrosion protection layers in pipelines transporting hydrocarbons - Giovanna Gabetta; Bernardo Molinas (Fracture and Structural Integrity)
Chemical reactions between carbon steel, water and chemical species produce corrosion layers (scales) on the internal surface of pipelines transporting hydrocarbons. Scales act as a diffusion barrier and prevent the progress of corrosion, a dangerous failure initiator. The protective film (10-100 μm thickness) can be removed locally by the action of the internal flow, or by other mechanisms. Adhesion with the substrate and the failure modes of the corrosion layer can be tested by indentation. Some results are presented of experiments performed on specimens with scales grown in a controlled environment.